THE ROLE OF XBRL IN PROMOTING THE QUALITATIVE CHARACTERISTICS OF ACCOUNTING INFORMATION: A STUDY OF THE EMPLOYEES' ATTITUDES AT FOUR BANKS LISTED IN THE IRAQI STOCK EXCHANGE - Abdullah Hussein Jameel (Scholar Express Journals, 2022)
This research aimed to shed light on the role of extensible business reporting language (XBRL) as one of the applications of modern information technology on enhancing the qualitative advantages of accounting informatics in a way that serves information users. The study was applied to 43 samples working at banks that were listed in the Iraqi stock exchanges.15-items questionnaire was designed to collect data from the participants. Findings showed that extensible business reporting language (XBRL) enhances the qualitative characteristics of accounting informatics, both in terms of presentation, quantity of information, timing of disclosure, impartiality and accuracy. Furthermore, XBRL encourages all interested transmitters and users of information to use this language. Furthermore, it was revealed that disclosure plays an effective role in enhancing the quality of financial information by providing two characteristics: transparency and reliability. Then the researcher sets following recommendations: The necessity of holding training courses and qualifying programs to train users how to use the extensible business reporting language (XBRL), the necessity of controlling the financial market in Iraq, and the necessity of issuing regulatory rules for the use of XBRL.
Keywords: Characteristics; qualitative; informatics; XBRL